FRI0435 Prognostic markers in juvenile vs. adult-onset ankylosing spondylitis. (23rd January 2014) - Jadon, D.; Hunt, L.; Arumugam, R.; Ramanan, A.; Sengupta, R.
Abstract : Background: Patients experiencing ankylosing spondylitis (AS) symptoms ≤16 years-of-age are classified as juvenileonset AS (JoAS), whilst those ≥17 years-of-age as adult-onset AS (AoAS). Studies from North America, China and Turkey suggest that JoAS and AoAS patients have differing clinical characteristics and functional outcomes; although results have been inconsistent. Objectives: This study compared JoAS vs . AoAS with respect toclinical, functional and genetic outcomes, and determined which factors were related to prognosis, as defined either by a poor BASFI (≥5) or by a history of AS-related surgery. Methods: 143 JoAS patients (103 males) were compared with 413 AoAS patients (307 males), both attending a tertiary care rheumatology hospital. A diagnosis of AS was made using the 1987 modified New York criteria. The following clinical parameters were recorded: sex; age at symptom onset (JoAS only); age at Rheumatologist-made diagnosis; the most recent BASFI, BASDAI, BASMI; HLA-B27 genotype status; the occurrence at any time point of psoriasis, uveitis, enthesitis, inflammatory bowel disease (IBD) or AS-related surgery (hip, shoulder or spinal). Two group comparisons were made with continuity-corrected Chi-squared, unpaired Student's t-tests and non-parametric Mann-Whitney U-tests. Results: At assessment, JoAS cases were only slightly younger than AoAS cases (mean age 49.0 vs . 51.9 years, respectively; mean difference in age 2.9 years, 95% CI 0.3-5.6 years). JoAS cases had a slightly longer mean disease duration since diagnosis [JoAS 26.0 years (SD 14.9), AoAS 19.3 years (SD 13.1)]. Comparing the JoAS and AoAS cohorts, the JoAS cases had had significantly more AS-related surgery (18.9% vs . 8.0%, respectively; p<0.001), and slightly more had had concurrent IBD (11.2% vs . 6.8%, respectively; p=0.13). No statistically significant difference was found between the two groups in terms of BASFI, ten BASFI domains, BASDAI, BASMI, sex distribution, HLA-B27 positivity, psoriasis, enthesitis, or uveitis (all cases or HLA-B27 positive cases only). Amongst the JoAS cases, those with a poorer BASFI (≥5.0) had symptom onset at a younger age than those with a better BASFI (<5.0) (mean age 12.5 vs . 13.4, respectively; trend p=0.08). JoAS cases with psoriasis were more likely to have a poor BASFI than those without psoriasis (55% vs . 25%, respectively; p=0.016). AoAS cases without uveitis were more likely to have a poor BASFI than those with uveitis (38% vs . 24%, respectively; p=0.007). Amongst the JoAS cases, those having had AS-related surgery had symptom onset at a younger age than those without surgery (mean age 12.5 vs . 13.3, respectively; trend p=0.18). JoAS cases with psoriasis were more likely to have had AS-related surgery than those without psoriasis (43% vs . 15%, respectively; p=0.006). No other prognostic markers were demonstrated. Conclusions: This study is the first to investigate a Northern-European population of Rheumatologist-diagnosed JoAS patients, and is the largest sample of prospectively-collected JoAS data published. JoAS and AoAS patients differed in terms of proceeding to AS-related surgery, and occurrence of IBD. In JoAS, younger age at symptom onset and occurrence of psoriasis, related to poorer prognosis. In AoAS, absence of uveitis related to poorer prognosis as measured by BASFI. Delay in diagnosis didn't correlate with prognosis. Disclosure of Interest: None Declared